Access to yellow fever travel vaccination centres in England, Wales, and Northern Ireland: A geographical study. Issue 18 (July 2017) - Petersen, Jakob; Simons, Hilary; Patel, Dipti
Abstract: Background: More than 700, 000 trips were made by residents in England, Wales, and Northern Ireland (EWNI) in 2015 to tropical countries endemic for yellow fever, a potentially deadly, yet vaccine-preventable disease transmitted by mosquitoes. The aim of this study was to map the geographical accessibility of yellow fever vaccination centres (YFVC) in EWNI. Methods: The location of 3208 YFVC were geocoded and the average geodetic distance to nearest YFVC was calculated for each population unit. Data on trips abroad and centres were obtained regionally for EWNI and nationally for the World Top20 countries in terms of travel. Results: The mean distance to nearest YFVC was 2.4 km and only 1% of the population had to travel more than 16.1 km to their nearest centre. The number of vaccines administered regionally in EWNI was found correlated with the number of trips to yellow fever countries. The number of centres per 100, 000 trips was 6.1 in EWNI, which was below United States (12.1) and above the rest of Top20 countries. Conclusions: The service availability was in line with demand regionally. With the exception of remote, rural areas, yellow fever vaccination services were widely available with only short distances to cover for the travelling public.